THE URGENCY OF REPRESENTATIVES ESTABLISHMENT OF WITNESESS AND VICTIMS PROTECTION AGENCY (LPSK) IN LOCAL AREAS - Lathifah Aini Rahman (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
Granting protection of witnesses and/or victims by LPSK that standing only in the capital of the Republic of Indonesia, Jakarta, there are problems to be debate among legal practitioners. The problem comes when a large number of requests that come to the LPSK is derived from various regions across Indonesia in the motherland, which often witnesses and/or victims who came from across the region who are far enough away will certainly require a large fee to head to Jakarta so that witnesses and/or victims are having trouble accessing request protection to LPSK. LPSK itself set in Article 11 of Law On Witnesses and Victims Protection. Representatives establishment office in fact already regulated on Article 11 paragraph (3), but in practice despite the fact a lot of the problems that come from the region, LPSK up to this moment does not form a representative in the local area.Keyword : Granting Protection, Witnesses and/or Victims, Witnesses and Victims Protection Agency (LPSK), Local Area.